Questions & Answers on Refrigerant Replacement - Flores, Rolando A.; Hayter, Richard B. (My University, 1991)
This publication outlines the major elements of the refrigerant replacement issue.
MF975_1991_02
Keywords: MF975; Equipment and Structures; MF